THE FRONT DOORBELLS IN TAT’JANA TOLSTAJA’S STORIES: THEIR DESIGN AND CULTURAL MEMORY - Giulia Baselica (Filolog, 2022)
In some stories by Tatyana Tolstaya, published between 2004 and 2015, of Soviet and post-Soviet setting, the doorbell, in the representation of living contexts, seems to take on a non-secondary significance. Sometimes, it is its aesthetic value to be highlighted; while, in other moments, it is its function to be emphasised. This article aims to investigate the meaning the doorbell acquires in Tolstaya’s narratives, the way it relates, each single time, to the surrounding system of objects, as well as with the main characters of the stories. Although its being a product of modern technology, the doorbell, located on the front door, connects to the threshold, a place steeped in stratified mythical and ancestral values.